COVID-19: Presumed Infection Routes and Psychological Impact on Staff in Administrative and Logistics Departments in a Designated Hospital in Wuhan, China - Luo, Li-Sha; Jin, Ying-Hui; Cai, Lin; Pan, Zhen-Yu; Zeng, Xian-Tao; Wang, Xing-Huan (Frontiers in Psychology, 2020)
Objective: To explore the presumed infection routes and psychological impact of COVID-19 on staff in administrative and logistics departments (ALDs). Methods: We gathered data from all 18 staffs with COVID-19 in ALDs in Zhongnan Hospital, China. The baseline, job before diagnosis, presumed infection environment, use of protective equipment and psychological status before and after diagnosis were collected and analyzed. 18 uninfected staff working alongside them in the same environment and 18 random matched infected doctors and nurses formed two control groups; then the psychological impact was compared between these three groups. Results: Of 18 staff, 88.89% were infected by the working environment in hospital, 9 had face-to-face conversations with doctors and nurses in their daily work. Many staff didn’t take any protective measures in their routine work. Before they were diagnosed, 12 staff were aware of the seriousness of the epidemic and most staff maintained a neutral attitude to the COVID-19 outbreak. 77.78% of staff experienced psychological stress or emotional changes after diagnosis, which were mainly caused by family health and disease related issues. Most of them managed their emotions by self-control and video call with family. There was no significant difference in psychological impact among the three groups, but uninfected staff were fully aware of the seriousness of the epidemic. They control emotion according to self-regulation and video call with family. Conclusions: Effective protective measures should be taken for staff in ALDs. Psychological interventions are very important to help infected staff in ALDs cope with psychological distress.